1999
DOI: 10.1152/jappl.1999.86.2.759
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of tidal volume by using transthoracic impedance variations in rats

Abstract: The application of impedance pneumography for monitoring respiration in small animals has been limited by problems with calibration. With improved instrumentation, we describe the calibration of tidal volume in anesthetized rats. The detection of changes in voltage, reflecting the electrical impedance variations associated with respiration, was optimized by using disposable adhesive silver-silver chloride electrodes, advanced circuitry, and analog-to-digital recording instrumentation. We found a linear relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Male Porton rats (200-330 g) were anesthetized with intraperitoneal methohexital sodium (60 mg/kg; Eli Lilly, Sydney, Australia) and pentobarbital sodium (40 mg/kg; Boehringer Ingelheim, Sydney, Australia) (12). The thorax and abdomen were shaved, and residual hair was removed (Veet hair removal cream, Reckitt and Colman Pharmaceuticals).…”
Section: Induction Of Lung Injurymentioning
confidence: 99%
See 2 more Smart Citations
“…Male Porton rats (200-330 g) were anesthetized with intraperitoneal methohexital sodium (60 mg/kg; Eli Lilly, Sydney, Australia) and pentobarbital sodium (40 mg/kg; Boehringer Ingelheim, Sydney, Australia) (12). The thorax and abdomen were shaved, and residual hair was removed (Veet hair removal cream, Reckitt and Colman Pharmaceuticals).…”
Section: Induction Of Lung Injurymentioning
confidence: 99%
“…The thorax and abdomen were shaved, and residual hair was removed (Veet hair removal cream, Reckitt and Colman Pharmaceuticals). A caudal vein and artery at the base of the tail were catheterized (12). Lines were fixed in place (Loctite 406 cyanoacrylate ester, Loctite Australia, Sydney, Australia), and heparinized saline (0.15 M, 2 U/ml) was infused (1 ml/h) to maintain the patency of the arterial line.…”
Section: Induction Of Lung Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…They found that transthoracic impedance in an open chest condition was greater in the expiratory state than in the inspiratory state. Researchers measured tidal volume (V T ) using transthoracic impedance variations in animals and found a linear relationship between change in impedance and V T [6,7]. Guha and Anand [8] investigated the EIP technique in comparison with electrical field plethysmography for evaluating cardiac and respiratory EIP pulses.…”
Section: Introductionmentioning
confidence: 99%
“…Impedance changes are a complex function of geometry and conductivity and studies have attempted to understand the relationship between impedance and physiological change [2]. The principle involved is based on the change in impedance that occurs across transthoracic electrodes during breathing [3].…”
mentioning
confidence: 99%